2010
DOI: 10.1109/tbcas.2010.2077290
|View full text |Cite
|
Sign up to set email alerts
|

A Vertically Integrated CMOS Microsystem for Time-Resolved Fluorescence Analysis

Abstract: We describe a two-chip micro-scale time-resolved fluorescence analyzer integrating excitation, detection, and filtering. A new 8×8 array of drivers realized in standard low-voltage 0.35-μm complementary metal-oxide semiconductor is bump-bonded to AlInGaN blue micro-pixellated light-emitting diodes (micro-LEDs). The array is capable of producing sample excitation pulses with a width of 777 ps (FWHM), enabling short lifetime fluorophores to be investigated. The fluorescence emission is detected by a second, vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…There are disadvantages, however, mainly associated with the near isotropic light emission pattern. Rae et al showed LEDs deposited on an ASIC and used in conjunction with a single-photon avalanche diode (SPAD) array to measure fluorescent dye [28]. Chediak et al provided a more compact implementation where a small LED was deposited on a PIN photodiode below a microfluidic channel [37].…”
Section: Ledsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are disadvantages, however, mainly associated with the near isotropic light emission pattern. Rae et al showed LEDs deposited on an ASIC and used in conjunction with a single-photon avalanche diode (SPAD) array to measure fluorescent dye [28]. Chediak et al provided a more compact implementation where a small LED was deposited on a PIN photodiode below a microfluidic channel [37].…”
Section: Ledsmentioning
confidence: 99%
“…With suitably fast electronics it is possible to shutter the light source and record the decay of the fluorescence [28,54,55].…”
Section: Temporalmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In this work, we demonstrate PL lifetime detection of low pressure explosive vapours of 1,4-dinitrobenzene (DNB) using thin films of a fluorescent conjugated copolymer combined with a very compact CMOS time-resolved fluorescence lifetime micro-system. 6 The fluorescent conjugated copolymer is a fluorene based copolymer "CDT Green (CDTG)" supplied by Cambridge Display Technology Limited (CDT Ltd). In addition to standard TCSPC measurements, we also use a two-gate rapid-lifetime determination (RLD) algorithm 7 to compute the PL lifetime in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Fast modulation speeds would also be advantageous for the use of these devices in time-resolved fluorescence measurements. 4 There is also great interest because of the importance of these processes in the effect known as "droop," where--except at very low current densities below a few tens of A cm À2 --the quantum efficiency of GaN LEDs decreases with applied current. 5 There is much controversy over the physical mechanisms causing droop.…”
mentioning
confidence: 99%